2021
DOI: 10.26855/er.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Learning Motivation and Inclusion Ability among Arab Minority Special Education Teachers in Israel

Abstract: This study examined the relationship between special education teachers' emotional intelligence and the learning motivation of students with specific learning disorders, moderated by the teachers' inclusion ability in regular education in Arab minority in Israel. The research setup is quantitative-correlative. The sample included 406 special education teachers (128 male and 278 female) in elementary and middle schools. The participants were asked to answer the following self-report questionnaires: sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…and their relationships. Studies have shown a significant positive correlation between EI and learning motivation, [33][34][35] indicating that they may play a chain mediating effect between PE and PSB. The higher the EI, the more effectively you can manage and use your emotions, generate positive emotions and relieve negative emotions.…”
Section: Chain Mediating Effect Of Ei and Pelmmentioning
confidence: 99%
“…and their relationships. Studies have shown a significant positive correlation between EI and learning motivation, [33][34][35] indicating that they may play a chain mediating effect between PE and PSB. The higher the EI, the more effectively you can manage and use your emotions, generate positive emotions and relieve negative emotions.…”
Section: Chain Mediating Effect Of Ei and Pelmmentioning
confidence: 99%
“…Within the teacher education context, there has been increasing interest on the impact EI will have on teachers' effectiveness and well-being. In fact, EI has been contextualised within the educational setting as the constellation of emotional, personal and social capabilities that affects one's interpersonal/intrapersonal competences, coping with stress and general mood (Danielle, 2019, as cited by Dallasheh, Zubeidat and Masri, 2021). To Allen, MacCann and Matthews, et al (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is possible because EI facilitates both intrapersonal and interpersonal well‐being of an individual. Regarding inclusive education, EI is significantly associated with teachers' inclusion ability (Dallasheh et al., 2021). No doubt, the flexibility and adaptability demands in teaching diverse students require possession of high EI among teachers.…”
Section: Literature Reviewmentioning
confidence: 99%